Microwave Assisted Extraction of Artemisia Pallens for Tyrosinase Inhibitory Activity - KANIMOZHI. P; K. ILANGO; ANUPAM CHOWDARY; ARUN. B; AMMAR MOHAMMED MUSA ADAM; A. NETHAJI (International Journal of Pharma and Bio Sciences, 2010)
The present study deals with the application of microwave as an extraction tool for extraction of phytoconstituents present in Artemisia pallens wall (compositae) and determination of tyrosinase inhibitory activity which serves as an useful target in the treatment of hyper pigmentation skin disorder. The percentage yield of extract obtained by microwave assisted extraction (MAE) of plant was found to be highly significant when compared to soxhlet extraction (SE) method. The tyrosinase inhibitory activity of MAE was found to be highly significant (p< 0.0001) when compared with that obtained by SE method.